“PrEP should be available all the time and everywhere”: A qualitative assessment of family planning and PrEP integration in Lesotho - Nonyana, Nyane-Matebello; Matete, Manthomeng; Lebetkin, Elena; Yacobson, Irina; Strachan, Molly; Ramapepe, Makeneiloe Anastasia; Malkin, Morrisa; Chakare, Tafadzwa (Frontiers in Reproductive Health, 2022)
Background: Lesotho has a high HIV burden, with women disproportionately affected. Increased access points for HIV prevention services, including oral pre-exposure prophylaxis (PrEP), should be considered. Using family planning (FP) settings for PrEP services may contribute to greater uptake of HIV prevention methods. Methodology: This formative qualitative assessment was conducted in Maseru District, Lesotho and included in-depth interviews with 15 key informants, 10 FP providers in public facilities and community sites, and 15 FP and PrEP clients from facility and community sites. Interviews were audio recorded and in lieu of producing transcripts, teams completed semi-structured data extraction tables after each interview. Findings were compiled and synthesized by participant group into matrices and themes identified through deductive and inductive analysis. Results: Policy makers were generally supportive of integration but felt hampered by lack of integration policies and separation of HIV and FP departments at Ministry of Health. Funders stressed the need for coordination among partners to avoid duplication of efforts. Partners felt clients would be interested in PrEP/FP integration and that PrEP demand creation and education were crucial needs. Most providers supported integration, stressing the potential benefit to clients. Barriers discussed included heavy workloads, staff shortages, training needs, separate registers for FP and PrEP, and commodity stock-outs. Providers discussed strengthening integrated services through training, increasing staffing, having job aids and guidelines, merging the FP and PrEP registers, and marketing services together to create demand for both. Clients were overwhelmingly willing to have longer visits to receive comprehensive services and were supportive of receiving PrEP services from FP providers. Clients not using PrEP expressed willingness and interest to use. Clients’ suggestions for successful integration included consulting with youth, conducting community outreaches, and improving provider availability. Conclusions: Existing FP platforms are established and well-utilized; thus providing opportunities for integrating PrEP. This assessment found support across all groups of respondents for providing PrEP within FP settings and identified a number of facilitators and barriers to integration. As PrEP rollout is relatively nascent in many countries, deepening the evidence base early will enable the utilization of findings to build stronger integrated programs with wider coverage.